TELOLET HORN SETTINGS BASED ON LEGISLATION IN INDONESIA - Yulia Hesti; Suta Ramadan; Aprinisa Aprinisa; Pika Sari (PRANATA HUKUM, 2023)
The use of telolet horns is currently increasingly popular in Indonesia. Telolet horn is a type of horn that produces a unique and distinctive sound. The phenomenon of "Om telolet om" or the use of the telolet horn makes many children carry out activities on the road that endanger traffic. Function of the Telolet Horn for Vehicles The horn functions as a means of communication with other road users and can make the surrounding community and road users happy. Setting Telolet Horn Based on Legislation in Indonesia where motorized vehicles operating on the road must have passed the vehicle-worthiness test and meet the technical requirements contained in other laws and regulations, one of which is the sound of a horn. The sound setting for the horn is regulated in Article 69 of Government Regulation Number 55 of 2012 concerning Vehicles, the sound of the horn as referred to in Article 64 paragraph (2) letter f has a minimum of 83 (eighty three) decibels or dB (A) and a maximum of 118 (one hundred eight fifteen) decibels or dB (A). The horn must be used according to its function so as not to harm road users and cause accidents to other motorists. It is hoped that the government will be able to make regulations specifically regarding the implementation of standard horn sounds.